Proteomics Challenges for the Assessment of Synuclein Proteoforms as Clinical Biomarkers in Parkinson’s Disease - Pons, Marie-Laure; Loftus, Neil; Vialaret, Jerome; Moreau, Stephane; Lehmann, Sylvain; Hirtz, Christophe (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease is a complex neurodegenerative disorder resulting in a multifaceted clinical presentation which includes bradykinesia combined with either rest tremor, rigidity, or both and also many non-motor symptoms. The motor features of the disorder are associated with the pathological form of alpha synuclein aggregates and fibrils in Lewy bodies and loss of dopaminergic neurons in the substantia nigra. It is a complex disease creating clinical challenges given that the disease is increasingly viewed as a group of underlying disorders with unique genetic, biological, and molecular abnormalities which are likely to respond differentially to a given therapeutic approach. At present, no therapy can slow down or arrest the progression of Parkinson's disease. There is a clear unmet clinical need to develop reliable diagnostic and prognostic biomarkers. When disease-modifying treatments become available, prognostic biomarkers are needed to support a definitive diagnosis and clinical intervention during the long prodromal period as no clinical implications or symptoms are observed. Robust diagnostic biomarkers would also monitor treatment response. Potential biomarkers for the sporadic form of Parkinson’s disease have mostly included synuclein species (monomer, oligomer, phosphorylated, Lewy Body enriched fraction and isoforms). In this review, we consider the analysis of synuclein and its proteoforms in biological sample in the context of neurodegenerative diseases by proteomics analysis which include immunoassay and mass spectrometry.